Audibilidade e consistência de uso do aparelho de amplificação sonora individual: repercussões na percepção de fala e vocabulário - Santos, Marina Marques dos (2024)
Introduction: In order to quantify the differences between individuals in the hearing access, to reflect the audibility and the use of the Personal Sound Amplification Device (PSAD) in a unique value it is utilized the calculus of “hearing dosage”, pointing that bigger values of the hearing dosage reflects in more hours of audibility. In this research it is amplified the relation between audibility and consistency of the usage through the concept of Hearing Dosage. Purpose: verify the relationship between audibility and consistency in the use of PSAD and the repercussions in the perception of the speech and vocabulary in children using personal sound amplification devices. Methods: It was a resumption of the population of Pereira’s (2023) study and analysed the data base containing information about the Speech Inteligibility Index (SII) for input sounds of 65 dBSPL (with or without PSAD) of 29 children with neurosensorial hearing loss and users of PSAD bilaterally with oral language, the number of hours per day of use of the device, four-tone average, results of the repetition of words with or without meaning in 65 dBSPL, Peabody Picture Vocabulary Test – PPVT. The consistency of the use was analysed through measuring the auditory dosage, which takes into account the average of use hours and the audibility with or without the device. Results: the PPVT has a positive correlation with the SII with the device at 65 dBSPL. The fourtone average has a significant negative correlation with the SII in both conditions; and the same happens, in a general sense, with the hours on daily usage. The dosage has a significant positive correlation with the SII and negative with the PTA. Conclusion: The receptive vocabulary tends to grow alongside with the audibility dosage increment. The listening experience, involving the audibility with or without the device and the consistency of the device daily use, must be considered throughout the whole process of the rehabilitation